2013
DOI: 10.2136/sssaj2012.0256
|View full text |Cite
|
Sign up to set email alerts
|

Winter Nitrate Leaching under Different Tillage and Winter Cover Crop Management Practices

Abstract: The potential for nitrate (NO3–) to leach is enhanced following cultivation of pastoral land, due to rapid mineralization of labile soil organic matter (SOM). In a 7‐yr field trial in New Zealand, we examined the impacts of tillage intensity [intensive (plowing to 20 cm), minimum, or no‐tillage] and winter cover crops (forage rape) on NO3– leaching following cultivation of permanent (sheep [Ovis aries]‐grazed) pasture to grow arable crops (the rotation included barley [Hordeum vulgare L.], wheat [Triticum aest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…However, the tillage pan may reduce root growth, reducing the effective soil volume (Nie, 2013). Although deep-ploughing is capable of overcoming these drawbacks, a potential risk is increased N leaching (Fraser et al, 2013). Our DBSR method successfully achieves deep-ploughing but may minimize N leaching .…”
Section: Discussionmentioning
confidence: 96%
“…However, the tillage pan may reduce root growth, reducing the effective soil volume (Nie, 2013). Although deep-ploughing is capable of overcoming these drawbacks, a potential risk is increased N leaching (Fraser et al, 2013). Our DBSR method successfully achieves deep-ploughing but may minimize N leaching .…”
Section: Discussionmentioning
confidence: 96%
“…Tribouillois et al (2018) and Wortman et al (2012) reported that the large quantity of soil water used by the cover crops, at the cost of the subsequent primary crop and immobilization of soil N due to incorporation of low quality cover crop residues into the soil, is also a major concern. Fraser et al (2013) found that tillage had some effects on N leaching, though the use of minimum tillage for autumn cultivation resulted in significantly less N leaching than either intensive or no-till. Fraser et al (2013) found that tillage had some effects on N leaching, though the use of minimum tillage for autumn cultivation resulted in significantly less N leaching than either intensive or no-till.…”
Section: Influences Of Management Soil and Climatic Zones On Covermentioning
confidence: 96%
“…Fraser et al (2013) and Hooker et al (2008) found that inter-annual weather variability and soil types explain the variability of cover crop effectiveness in the temperate regions. Fraser et al (2013) and Hooker et al (2008) found that inter-annual weather variability and soil types explain the variability of cover crop effectiveness in the temperate regions.…”
Section: Nghgb (Mean ± Sd)mentioning
confidence: 99%
“…With this technique, it is possible to achieve greater production of vegetal biomass to cover the soil Ceccon et al, 2013;Crusciol et al, 2013), and it also allows the establishment of pastures for livestock Fisher et al, 2012;Borghi et al, 2013). This technique can provide many benefits for the soil-plant system, such as reducing soil loss by erosion (Montenegro et al, 2013;Lima et al, 2014), a reduction in the occurrence of weeds (Amossé et al, 2013;Scopel et al, 2013) and the maintenance of a vegetated area, allowing for greater nutrient cycling and the reduction of nutrient loss in the off-season (Fraser et al, 2013;Hashemi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%